"أثر البحث والتطوير على النمو الاقتصادي في البلدان الصناعية " - عبد الغني, عبيدي; عبد العالي, بوطيب; محمد, بالهادي (جامعة الوادي university eloued, 2020)
تهتم هذه المذكرة البحثية بدراسة العلاقة الكمية بين البحث والتطوير كمتغير مستقل ومتغير النمو الاقتصادي كمتغير تابع ، باستعمال المعطيات الإحصائية للبلدان الصناعية خلال الفترة الممتدة بين (1996 – 2018) وقد تطرقنا في هذه المذكرة البحثية لمفهوم البحث والتطوير كمتغير تابع، مرشح للتأثير على النمو الإقتصادي، كما تطرقنا إلى تطور النظريات المفسرة للنمو ووقفنا على أهمية المقاربات الحديثة لمفهوم النمو – نظريات النمو الداخلي المنشأ - مع التركيز على ما النظريات الحديثة التي تعتمد على البعد التكنولوجي، والبحث والتطوير في أطروحاتها. لنتوصل إلى النموذج المقدر في حالة البلدان الصناعية والذي يوضح العلاقة الكمية بين البحث والتطوير والنمو الاقتصادي؛ هدفنا الأساسي من خلال هذه الورقة البحثية هو توضيح العلاقة الكمية المباشرة بين النمو الإقتصادي والبحث والتطوير في حالة البلدان الصناعية ومن النتائج التي تحصلنا عليها من خلال هذه المذكرة البحثية وجود علاقة كمية مباشرة بين البحث والتطوير والدخل- كمتغير لقياس النمو الإقتصادي - في حالة البلدان الصناعية .This research note is concerned with studying the quantitative relationship between research and development as an independent variable and the economic growth variable as a dependent variable, using statistical data for industrialized countries during the period between (1996 - 2018). In this research note, we discussed the concept of research and development as a dependent variable, a candidate to influence economic growth, We also touched on the development of the explanatory theories of growth and the importance of modern approaches to the concept of growth - endogenous growth theories - with a focus on what modern theories depend on the technological dimension, and research and development in their theses. Let us arrive at the estimated model in the case of industrialized countries, which shows the quantitative relationship between research and development and economic growth; Our main goal through this research paper is to clarify the direct quantitative relationship between economic growth and research and development in the case of industrialized countries, and from the results we obtained through this research note, there is a direct quantitative relationship between research and development and income - as a variable to measure economic growth - in the case of industrialized countries.
مذكرة ماستر اقتصاد كمي
Keywords: البحث - التطوير - النمو الاقتصادي -للبلدان الصناعية; research - development - economic growth - industrialized countries